Do you reap what you sow? The relationship between primary school students' self-regulated learning and student, teacher, and school determinants. Issue 1 (2nd January 2021) - Heirweg, Sofie; De Smul, Mona; Merchie, Emmelien; Devos, Geert; Van Keer, Hilde
ABSTRACT: Notwithstanding the importance of self-regulated learning (SRL), several studies have shown that schools and teachers struggle to promote SRL. Also, many students encounter difficulties with effectively regulating their learning. Therefore, the present study explores potential hampering and supporting factors for SRL implementation by investigating the interplay between determinants at the school, teacher, and student level. Survey data were gathered from 1, 796 upper primary school students and their 110 teachers in 43 primary schools. The results of the multilevel path analyses underline the importance of reflective dialogue between team members because it is positively and directly related to teachers' SRL self-efficacy and indirectly to their self-reported SRL promotion. At the teacher level, a strong interrelatedness is shown between teachers' beliefs, self-efficacy, and SRL promotion. Finally, this study provides evidence for a significant but mostly negative relation between teachers' SRL promotion and students' metacognition and motivation, taking into account students' background characteristics.